MEDIA PEMBELAJARAN TEMATIK: KAMAR MANDIKU, TEMPAT BELAJARKU - Tiara Sevi Nurmanita; Siti Nurwatin (PROCEEDING UMSURABAYA, 2022)
The researchâ€™s purpose to analyze using of the surrounding environment as student learning media. The bathroom is one part in the student's home. The bathroom can be an alternative for the student learning process. The various parts of the bathroom make it an alternative to the thematic learning process. Therefore, an experiment about use the bathroom as student learning media. The first step was using school bathrooms and the students can continue their learning in their home independently. The results obtained the first time, students have a sense of care to cleanliness and saving water.. The concept of the bathroom as a place to study, that can use floor tiles or bath measurements. Students can also get story inspiration by learning to describe the bathroom atmosphere. The use of the study room in the bathroom is certainly a breakthrough form of thematic learning media that is friendly and of course cheap. In addition, the use of learning media is not monotonous in the classroom. That's because learning can be done with anyone, anytime and anywhere.Â Keywords: instructional media; bathroom; environmentÂ